Social media design and new requirements for communications - Abeldaeva Ш.А.; Ramazan А.А. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2023)
The article defines the level of use of digital technologies in Kazakhstan, pays attention to the ways of design of social networks, and draws conclusions on their ultimate goals. The influence of social network design on society as a whole and design elements that should be taken into account when creating them are studied. Information about the design of digital technologies in Kazakhstan is presented, their tools and applications are studied, ways of developing the design of social networks are considered. Currently, due to the increased interest in the design of social networks, design research in this area is becoming increasingly widespread. The design of social networks has a direct impact on consumers and businesses, it is a modern technological sphere that contributes to the development of marketing and design.